Effectiveness of Structured Protocol on Knowledge in Prevention of Local Complications related to Peripheral Intravenous Cannulations, Injection and Infusion Among Staff Nurses. - SUZY LEWIS CHEN,; DR. P. MANGALA GOWRI,; DR. ARUNA, (International Journal of Pharma and Bio Sciences, 2018)
Intra vascular devices are used to administer intravenous fluids, medications, blood products to the ill patients. The placement of peripheral venous catheter is an important task and one of the most frequent nursing procedures. It is a clinical skill that is increasingly becoming part of nurses remit because of a number of changes in the hospital practice. (i) Assess the pre test level of knowledge among staff nurses in both the experimental and control group.(ii) To determine the effectiveness of structured protocol on the post test level of knowledge among the experimental group. (iii) Associate the post test level of knowledge with selected demographic variables among staff nurses. A quasi experimental design. Effective mean score is 4.65 and standard deviation is12.81. The paired t-test value was 9.04 and P value was 2.98. Level of significance is P<0.001. Structured protocols were found to be effective in improving the knowledge related to peripheral catheters among the staff nurses. The implementation of the protocol helped to assess the practicability and feasibility in a clinical setting. Nursing practice no longer relies on tradition or ritual: instead, it is based on research and empirical evidence. This study has also clearly shown the need for having a structured protocol in order to prevent the local complications. It is also necessary that every patient receiving peripheral intravenous therapy need to be cared based on the protocol, which includes the standard steps for each procedure. To undertake this skill, it is important that nurses receive the appropriate education and training.